Development of State Civil Apparatus Religiosity through the Taklim Assembly of Karanganyar Regency in 2022-2023 - Muhammad Ja’far Nashir; Dinar Bela Ayu Naj’ma (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The importance of coaching in the State Civil Apparatus is because it can spur development in various businesses for each civil servant, as well as the smooth implementation of its work programs to achieve effective targets. The objectives of this study are (1) to Analyze the Religiosity of the State Civil Apparatus in Karanganyar Regency, (2) to analyze the Development of Religiosity of the State Civil Apparatus Nahdlatul Ulama Taklim Council, Muhammadiyah Taklim Council, Nurul Iman Taklim Council in Karanganyar Regency in 2022-2023, (3) Analyzing problems and solving problems of State Civil Apparatus Religiosity Development through the Nahdlatul Ulama Taklim Council, Muhammadiyah Taklim Council, Taklim Nurul Iman Assembly in Karanganyar Regency in 2022-2023. This study used a qualitative descriptive method. The research samples are civil servants actively participating in studies at the Nurul Iman Taklim Council, Muhammadiyah Taklim Council, and Nahdatul Ulama Taklim Council in Karanganyar Regency, Central Java Province, in 2022-2023. Data collection techniques include observation and documentation interviews. Data analysis techniques are collection, reduction, presentation, and conclusions. The conclusions from the results of this study are (1) the religiosity of the State Civil Apparatus in Karanganyar Regency is very good in the dimension of understanding and intellectual dimension; (2) The development of the religiosity of the State Civil Apparatus through the Taklim Council in Karanganyar Regency has been carried out in a structured and systematic manner, so that the civil servants of Karanganyar Regency have a good nature of religiosity, proven in the world of work ASN works responsibly, calmly, professionally and accountably; (3) Problems and problem solving The development of religiosity of the state civil apparatus through the taklim assembly in Karanganyar Regency essentially starts from the problems of civil servants personally carried away when participating in studies, thus making them not concentrated, bored and chatting individually. With the strengthening and deepening of religious knowledge and science carried out by the Taklim Council rhythmically and continuously, these problems can be resolved adequately based on the problems of each of these individuals.